Non Invasive Foetal Monitoring with a Combined ECG - PCG System - Ruffo, Mariano; Cesarelli, Mario; Jin, Craig; Gargiulo, Gaetano; McEwan, Alistair; Sullivan, Colin; Bifulco, Paolo; Romano, Maria; Shephard, Richard W.; Schaik, André van (IntechOpen, 2011)
None